PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK SISWA DI SDIT MUTIARA RAHMAH BALIKPAPAN - Dhela Nur Hayati; Iskandar Yusuf (Cahaya Ilmu Bangsa Institute, 2025)
Education not only aims to enhance students' intelligence but also to shape good character and moral values. Therefore, the role of Islamic Religious Education (IRE) teachers is crucial in shaping students' morals at school. This study aims to identify the contributions of IRE teachers in the moral development of students at SDIT Mutiara Rahmah Balikpapan. Using a field research approach and qualitative methods, data were collected through observation, interviews, and documentation, and then analyzed to draw conclusions. The findings of the study are as follows: 1) IRE teachers play the roles of guides, educators, motivators, facilitators, and evaluators in shaping students' morals, implemented through the habituation of religious activities at school. 2) The strategies employed by IRE teachers include regular engagement in various religious activities to support moral development. 3) The moral development of 2nd-grade students is progressing well, as seen from their habit of participating in religious activities, although some students still require further guidance.